The brilliant light of Amber sunrise - Crow, Matthew 1987- (Simon Pulse, 2015)
Life threatening cancer brings Francis and Amber together. But Francis's recovery is taking a different path from Amber's. He's actually getting better. And although he knew who he was before cancer, before Amber, now he has no idea how to live...or how to let go....